Application of 87Sr/86Sr ratios to discerning groundwaters from different lithostratigraphic units in the Southwest coastal region of South Africa - Gcakasi, Monis Nolitha (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.